2014
DOI: 10.1111/anae.12531
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ropivacaine concentration on the spread of sensory block produced by continuous thoracic paravertebral block: a prospective, randomised, controlled, double‐blind study

Abstract: SummaryFactors affecting the distribution of continuous thoracic paravertebral block have never been examined. We designed this prospective, double-blind study to check whether continuous thoracic paravertebral block with a higher ropivacaine concentration would provide a wider segmental sensory block spread. Sixty consecutive patients undergoing pulmonary lobectomy or segmentectomy were randomly allocated to receive continuous paravertebral infusion of either 0.2% or 0.5% ropivacaine (6 ml.h

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 24 publications
2
21
0
Order By: Relevance
“…Yoshida et al studied the effect of 0.2% and 0.5% ropivacaine on segmental spread after continuous TPVB and found no significant difference related to the concentration used [22]. We too observed sensory block of 7-10 segments with 20 ml of 0.5% ropivacaine.…”
Section: Discussionsupporting
confidence: 42%
“…Yoshida et al studied the effect of 0.2% and 0.5% ropivacaine on segmental spread after continuous TPVB and found no significant difference related to the concentration used [22]. We too observed sensory block of 7-10 segments with 20 ml of 0.5% ropivacaine.…”
Section: Discussionsupporting
confidence: 42%
“…If a hyperechoic flash by the air-saline mixture was not observed in the TPVS, the catheter was withdrawn by 0.5 cm and the same amount of the mixture was reinjected. If a hyperechoic flash was not observed when the catheter length within the TPVS was 3 cm, the catheter was removed and reinserted 7. After the catheter tip position was confirmed to be in the TPVS, to exclude intravascular migration of the catheter tip, we performed the negative aspiration test followed by injection of 2% lidocaine with 1:200 000 epinephrine 3 mL 10 11.…”
Section: Methodsmentioning
confidence: 99%
“…Bolus injection of a local anesthetic followed by continuous infusion is the standard technique of thoracic paravertebral block for post-thoracotomy analgesia 4–6. However, the range of anesthetized dermatomes becomes gradually narrower when the local anesthetic is administered at a constant rate 7. Although the addition of a bolus injection of local anesthetic to continuous infusion or repeated bolus injections can maintain the range of anesthetized dermatomes of thoracic paravertebral block in theory, the effect of repeated intermittent thoracic paravertebral injection of the local anesthetic on the time-dependent change in the number of anesthetized dermatomes has not been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, regarding the amount of local anesthesia, we decided to use a higher concentration of local anesthesia when we initiated the use of thoracic PVB at our hospital, because several studies have shown that a greater amount of local anesthetic was required in the PVB group than in the EDA group [4, 8, 2426]. However, some reports have already demonstrated that higher concentration and rate were not required in PVB groups to achieve the same effect [2729]. Therefore, the amount of ropivacaine and fentanyl in the PVB group can be reduced to the same level as in the EDA group.…”
Section: Discussionmentioning
confidence: 99%